2011
DOI: 10.1021/es201193s
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation and Effects of CdTe/CdS Quantum Dots on Chlamydomonas reinhardtii – Nanoparticles or the Free Ions?

Abstract: In order to properly assess the environmental risk of engineered nanoparticles (ENP), it is necessary to determine their fate (including dissolution, aggregation, and bioaccumulation) under representative environmental conditions. CdTe/CdS quantum dots (QD), such as those used in medical imaging, are known to release Cd(2+) due (mainly) to the dissolution of their outer shell. In this study, Chlamydomonas reinhardtii was exposed to either a soluble Cd salt or QD at similar concentrations of total Cd. Free Cd c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 111 publications
(80 citation statements)
references
References 39 publications
1
78
1
Order By: Relevance
“…In order to ensure that the exposure conditions elicited a response while minimizing secondary effects and lethality, conditions were selected by considering prior reports of their toxicological effects for nAg (31), nTiO 2 (1), nZnO (32), and QDs (33). The physicochemical properties and effects of the NPs change following their aggregation (17,34), dissolution (12,20,70), or coating with biological substances (e.g., proteins [35]), since these parameters affect the interfacial properties, including the rates of surface-mediated reactions, dissolution, redox reactions, and generation of ROS (36). Therefore, the sizes of the NPs were quantified in the exposure medium (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to ensure that the exposure conditions elicited a response while minimizing secondary effects and lethality, conditions were selected by considering prior reports of their toxicological effects for nAg (31), nTiO 2 (1), nZnO (32), and QDs (33). The physicochemical properties and effects of the NPs change following their aggregation (17,34), dissolution (12,20,70), or coating with biological substances (e.g., proteins [35]), since these parameters affect the interfacial properties, including the rates of surface-mediated reactions, dissolution, redox reactions, and generation of ROS (36). Therefore, the sizes of the NPs were quantified in the exposure medium (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…C. reinhardtii was added at a cell density of 1 cm 2 ml Ϫ1 to five flasks (300 ml) containing the exposure medium and one of the following: control (no NP), 1 mg liter Ϫ1 nTiO 2 , 1 mg liter Ϫ1 nZnO, 1 mg liter Ϫ1 nAg, or 0.125 mg liter Ϫ1 QDs. Preliminary experiments showed that the lower concentration of QDs still induced significant changes at the transcriptomic level (12). Cell densities, sizes, and surface distributions were determined using a Coulter Multisizer 3 particle counter (50-m orifice; Coulter Electronics).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CdSe, CdTe, and CdS coated with hydrophilic deprotonated thiol ligands were shown to be unstable at a relatively low pH range, between 2 and 7, because of the dissociation of the QD-ligand coordinating bonds from the QD surface (Aldana et al 2001(Aldana et al , 2005. Studies on QD-organism interactions also have indicated that QD toxicity may at least be partially attributed to the release of toxic ions (Kloepfer et al 2003;Mahendra et al 2008;Priester et al 2009;Aruguete et al 2010;Domingos et al 2011). Aruguete et al (2010) observed an increase of the released Cd from CdSe/CdS QD when incubated in the Pseudomonas aeruginosa growth medium in presence of nitrilotriacetic acid (NTA), which was explained by the NTA ability to chelate Cd ion.…”
Section: Responsible Editor: Philippe Garriguesmentioning
confidence: 99%
“…Work using this model organism has shown toxicity and uptake of silver nanoparticles, quantum dots, and titanium dioxide nanoparticles [15][16][17]. Additionally, C. reinhardtii has been used in finding toxic effects of SWCNT poorly suspended in solution with no surfactant [18].…”
Section: Introductionmentioning
confidence: 99%